Investigation of Mating Pheromone–Pheromone Receptor Specificity in Lentinula edodes - Kim, Sinil (Genes (Basel), 2020)
The B mating-type locus of Lentinula edodes, a representative edible mushroom, is highly complex because of allelic variations in the mating pheromone receptors (RCBs) and the mating pheromones (PHBs) in both the Bα and Bβ subloci. The complexity of the B mating-type locus, five Bα subloci with five alleles of RCB1 and nine PHBs and three Bβ subloci with 3 alleles of RCB2 and five PHBs, has led us to investigate the specificity of the PHB–RCB interaction because the interaction plays a key role in non-self-recognition. In this study, the specificities of PHBs to RCB1-2 and RCB1-4 from the Bα sublocus and RCB2-1 from the Bb sublocus were investigated using recombinant yeast strains generated by replacing STE2, an endogenous yeast mating pheromone receptor, with the L. edodes RCBs. Fourteen synthetic PHBs with C-terminal carboxymethylation but without farnesylation were added to the recombinant yeast cells and the PHB–RCB interaction was monitored by the expression of the FUS1 gene—a downstream gene of the yeast mating signal pathway. RCB1-2 (Bα2) was activated by PHB1 (4.3-fold) and PHB2 (2.1-fold) from the Bα1 sublocus and RCB1-4 (Bα4) was activated by PHB5 (3.0-fold) and PHB6 (2.7-fold) from the Bα2 sublocus and PHB13 (3.0-fold) from the Bα5 sublocus. In particular, PHB3 from Bβ2 and PHB9 from Bβ3 showed strong activation of RCB2-1 of the Bβ1 sublocus by 59-fold. The RCB–PHB interactions were confirmed in the monokaryotic S1–10 strain of L. edodes by showing increased expression of clp1, a downstream gene of the mating signal pathway and the occurrence of clamp connections after the treatment of PHBs. These results indicate that a single PHB can interact with a non-self RCB in a sublocus-specific manner for the activation of the mating pheromone signal pathways in L. edodes.